Sports journalism and transmediation: The coverage of four journalists on TikTok during 2024 - Inca León, Patricia (#PerDebate, 2025)
Sports journalism in Ecuador is undergoing a digital transformation in which female journalists use transmedia strategies to carve out a space in this traditionally masculinized field. This study examines how four Ecuadorian professionals (Maite Montalvo, Analí Vasco, Daniela Romero, and Soledad Rodríguez) are using TikTok alongside media to cover sporting events in 2024, with the specific objective of analyzing the characteristics of their transmedia narratives and their impact on building their personal brand. Through virtual ethnography and content analysis of 435 TikTok videos, combined with the journalists’ media output, the research reveals distinct patterns: while TikTok is used for immediate, high-engagement content, the media outlets offer in-depth analyses. International coverage, in particular, accounted for a high percentage of the recorded interactions
Keywords: Ecuador; mass media; traditional media; social media; journalism; Gender; sports; transmedia storytelling